Synthesis and molecular structure of trinuclear mixed-metal cluster cations containing arene and hydrido ligands - Romakh, Vladimir; Therrien, Bruno; Süss-Fink, Georg (My University, 2006)
The mixed-metal trinuclear cluster cations [H3Ru2(C6Me6)2Os(C6H6)(O)]+ (1), [H3Ru2 (1,2,4,5-C6H2Me4)2Os(p-MeC6H4iPr)(O)]+ (2) and [H3Ru2 (1,2,4,5-C6H2Me4)2Os(C6H6)(O)]+ (3) have been synthesised from the corresponding dinuclear precursors [H3Ru2(arene)2]+ and the corresponding mononuclear complexes [Os(arene)(H2O) 3]2+, isolated and characterised as the tetrafluoroborate and hexafluorophosphate salts. The cations 1, 2 and 3 are heteronuclear analogues of the cluster cation [H3Ru3(C6H6)(C6Me6)2 (O)]+ that possesses a homonuclear metallic core. The single-crystal X-ray structure analyses of [1][BF4], [2][PF6] and [3][PF6] reveal an equiangular metal triangle despite the presence of an osmium atom in the metallic core.
Keywords: arene ligand; cluster; hydride; osmium; ruthenium